Dermatoglyphic Patterns, 2D:4D Digit Ratio, and Body Mass Index among Tuberculosis Patients: A Hospital-Based Case-Control Study at Infectious Disease Hospital, Kano, Nigeria - I., Salman J.; I., Badamasi M.; O., Mosugu O.; F., Otashu K.; J., Tongle N.; M., Jibaniya G.; W., Alfred A.; D., Izam E.; S., Katchin E.; O., Ajayi S. (Darul Yasin Al Sys, 2025)
Nigeria ranks highest in Africa and sixth globally in the incidence of newly diagnosed Mycobacterium tuberculosis cases, with over 600,000 new cases reported annually and a mortality rate of 20 per 100,000 population. Emerging evidence suggests that dermatoglyphic patterns, digit ratio (2D:4D), and body mass index (BMI) may serve as potential biomarkers for disease susceptibility. This hospital-based case-control study was conducted at the Infectious Disease Hospital (IDH) in Kano, Nigeria, to compare dermatoglyphic features, digit ratios, and BMI between tuberculosis (TB) patients and healthy controls. A total of 200 participants—comprising 100 confirmed TB patients and 100 age- and sex-matched healthy controls—were recruited through convenience sampling. Fingerprints were digitally captured and classified using Langerberg and Adebisi’s criteria, with ridge counts determined via the Okajima method. Digit lengths were measured using a Vernier caliper, and BMI was calculated following standard anthropometric procedures. Results revealed significantly lower ridge densities in the left index, right ring, right middle, and left little fingers of TB patients compared to controls. TB patients also exhibited reduced radial ridge counts in the left thumb, index, middle, ring, and little fingers, as well as decreased ulnar ridge counts in the right index finger. Among fingerprint patterns—loop, whorl, and arch—the arch pattern occurred with significantly higher frequency bilaterally in TB patients. No statistically significant differences were found in 2D:4D digit ratios between groups. However, BMI values were notably lower in the TB cohort. These findings suggest that specific dermatoglyphic traits and lower BMI may serve as supplementary indicators of susceptibility to tuberculosis. Further large-scale studies are needed to confirm these associations and evaluate their potential in early risk identification.